Metabolite Fingerprints and Chemometrics-Based Approach for Discrimination of Miana (Coleus scutellarioides) Variety: Authentication of Traditional Medicine Raw Materials - Syahruni, Reny; Umar, Abdul Halim; Lido, Fenisia (Universitas Tadulako, 2024)
Background: Miana (Coleus scutellarioides) is a plant from the Lamiaceae family consisting of several varieties that are traditionally used as medicinal materials, especially its leaves. Objectives: The study aims to classify/discriminate miana varieties based on FT-IR spectroscopic profiles and chemometric analysis (PCA, HCA, and PLS). Material and Methods: There are four samples used in this study, namely purple miana, green miana, batik miana, and combination miana (combination colour). The powders of the four miana samples were analyzed using FT-IR spectroscopy, then analyzed by chemometric techniques using PCA, HCA, and PLS to see the clustering patterns and functional group markers of the samples. Results: Based on chemometric analysis of FT-IR data, the four species of miana leaves showed grouping based on their varieties, respectively. The total PC value was 99.5% (PC-1 97.7% and PC-2 1.8%). HCA analysis at a distance of 2.5 resulted in 4 groups: a (DMB, DMK, and DMU), b (DMU and DMK), c (DMU and DMK), and d (DMH). PLS analysis using VIP scores showed C–H and C=O groups with values > 1. Conclusions: The combination of FT-IR and chemometrics can be applied to discriminate miana samples in quality control and authentication of traditional medicine raw materials. Analysis with LC-MS/MS and NMR instruments is needed for further analysis and support compounds that have the potential to distinguish the four miana varieties.